STUDI EVALUASI KINERJA SUMBER DAYA MANUSIA (SDM) DALAM MENGELOLA OBYEK WISATA TAMAN MARGASATWA MANGKANG KOTA SEMARANG - Christine Diah Wahyuningsih; Susilo Endrawanti (Serat Acitya, 2015)
ABSTRACT Mangkang Zoological Garden in Semarang is one of the pleasure park for the citizen which lies strategically on the Semarang-Kendal highway at Km post 17. Achievable ticket price is Rp.5000,-. Riding on elephant, to ride on water tricycle, horse riding, flying fox are Rp.3000,-. Over this condition, it is hoped that visitor would rise from year to year.   In this website, the organizer offers the most completed recreation for kids, cheap, clean and tidy. In fact, the number and kind of animal are limited, dirty, rubbish everywhere, settees are not well maintained, the garden at each pavilion are not tidy. The visitor decreases from year to year, in 2011 number of visitors are 267.346, while in 2012 become 243.883. Based on the above conditions, writers were interested in conducting a research on evaluation of the performance in managing Mangkang Zoological Garden Semarang as a tourism’s object. The aims of this research are: 1)to indicate the human resources who managing this tourism’s object, 2)to indicate why this tourism’s object is not interested by the people yet. The usefullness: 1)to increase the conception and dan try to help in problem solving in relation with human resources particularly, 2)giving input and consideration to the concerned official agency. The type of research is descriptive qualitative description one. Methods of data collection, observation, in-depth interviews with 10 informants consisting of Head of UPTD, vet, cleaning service coordinator, ticketing coordinator, security person, animal tamer, animal keeper, garden coordinator, medical veterinarinist, paramedical veterinarinist. Writers also hold an interview with Head of Kepala Dinas Kebudayaan Dan Pariwisata Kota Semarang as a key-person. The interpretation of the results of interviews with informants were used as an analysis of the data.   The results of research and fact findings are: 1)performance of human resources in managing animal, it is found that number of person in compared with width of animal’s area is not adequate, since area of 10 Ha should be covered by 47 persons (25 official servant and 22 honorary employee=HorDis); 2)grade of education point of view, 8,51% college degree, dan 91,49% honorary employee are upper secondary school grade; 3)lack of security effort over all animal area, garden hall and whole garden area in general; 4) no clear organization chart to support good management effort, since all people are liable to head of UPTD directly. keyword: performance, human resources, zoological garden